The essence of al-wadi'ah al-mashrifiyyah - Waluya, Atep Hendang (Journal of Islamic Economics Lariba, 2017)
The general objectives of Allah the Merciful and the Compassionate to make law is to accomplish human welfare by ensuring the values of dharuriyah (the essential), as well as hajiyyah (the complementary) and tahsiniyyah (the desirable). Besides protecting assets and properties, one of the advantages in the implementation of wadiah is fulfilling humans’ needs as well as eliminating their distress. Wadiah is considered a trust, in which it will change into a priority once it has been deposited. In the midst of its development, wadiah is not only practiced between individuals, but also institutions, including banking institutions. Unlike the meaning of wadiah in terms of fiqh (Islamic jurisprudence), wadiah in banking is considered as debts based on the interpretation of a number of contemporary Islamic jurists. This is due to the utilization of the fund by banking institutions. Furthermore, the institutions are also responsible for the loss of financial deposit, whether it is due to intentional aspects or not, as well as whether the financial deposit is intentionally lost or not. Moreover, the sole purpose and significance become the emphasis rather than its meaning (lafadz) in the process of its covenant.